The International Ice Charting Working Group: the first twenty-five years - Falkingham, John (Frontiers in Marine Science, 2025)
Since 1999, the International Ice Charting Working Group (IICWG) has successfully worked as a forum for the operational ice services and helped them to better meet the needs of their national and international maritime clients through coordination and cooperation in data sharing, standards, training, product development, and research activities. The annual meeting has proven to be a valuable opportunity for the national ice services to meet, along with their partners and clients, to share information about new research developments, implementation successes and failures, and advances in ice information products and services. This paper presents a brief overview of the first twenty-five years of the IICWG, including its raison d’être, the history of its formation, its organization, and its accomplishments.